Non cystic fibrosis bronchiectasis: A longitudinal retrospective observational cohort study of Pseudomonas persistence and resistance. Issue 6 (June 2015) - McDonnell, Melissa J.; Jary, Hannah R.; Perry, Audrey; MacFarlane, James G.; Hester, Katy L.M.; Small, Therese; Molyneux, Catherine; Perry, John D.; Walton, Katherine E.; De Soyza, Anthony
Summary: Background: The hallmark of non-cystic fibrosis bronchiectasis is recurrent bronchial infection, yet there are significant gaps in our understanding of pathogen persistence, resistance and exacerbation frequencies. Pseudomonas aeruginosa is a key pathogen thought to be a marker of disease severity and progression, yet little is known if the infection risk is seen in those with milder disease or if there is any potential for eradication. These data are important in determining risk stratification and follow up. Methods and patient cohort: A retrospective review of consecutive adult patients attending a specialist UK bronchiectasis clinic over a two-year recruitment period between July 2007 and June 2009 was performed. Analysis of our primary outcome, longitudinal microbiological status, was recorded based on routine clinical follow-up through to data capture point or date of death. Patients were stratified by lung function and infecting organism. Results: 155 patients (mean (SD) age 62.2 (12.4) years; 60.1% female) were identified from clinic records with microbiological data for a median (IQR) follow up duration of 46 (35–62) months. Baseline mean FEV1 % predicted was 60.6% (24.8) with mean exacerbation frequency of 4.42/year; 73.6% reported 3 or more exacerbations/year. Haemophilus influenzae was isolated in 90 (58.1%) patients and P. aeruginosa in 78 (50.3%) patients with persistent infection in 51 (56.7%) H. influenzae and 47 (60.3%) P. aeruginosa, respectively. Of the P. aeruginosa colonised patients, 16 (34%) became culture negative on follow-up with a mean of 5.2 negative sputum cultures/patient. P. aeruginosa was isolated from 5 out of 39 patients (12.8%) with minimal airflow limitation as compared to 18 out of 38 patients (47.4%) with severe airflow limitation. Although hospital admissions were significantly higher in the P. aeruginosa infected group (1.3 vs. 0.7 admissions per annum, p = 0.035), overall exacerbation rates were the same (4.6 vs. 4.3, p = 0.58). Independent predictors of P. aeruginosa colonisation were low FEV1 % predicted (OR 2.46; 95% CI 1.27–4.77) and polymicrobial colonisation (OR 4.07; 95% CI 1.56–10.58). 17 (11%) patients were infected with multi-resistant strains; however, none were pan-resistant. Conclusions: P. aeruginosa is associated with greater persistent infection rates and more hospital admissions than H. influenzae . Exacerbation rates, however, were similar; therefore H. influenzae causes significant out-patient morbidity. P. aeruginosa infection occurs across all strata of lung function impairment but is infrequently multi-resistant in bronchiectasis. Careful microbiology follow up is required even in those with well-preserved lung function.